2020
DOI: 10.1007/s00520-020-05422-z
|View full text |Cite
|
Sign up to set email alerts
|

A portable survivorship care plan: a tool that helps educate and improve knowledge in childhood cancer survivors

Abstract: Purpose There is a growing population of survivors of childhood cancer at risk for late effects that can affect their overall quality of life. There is evidence that they have inadequate knowledge about their diagnosis, treatment, and subsequent late effects. A randomized study was conducted to determine if a portable credit card-sized plastic card, the "Survivor Healthcare Passport," improved the survivor's knowledge of diagnosis, treatment, risks, and follow-up care. The study included 126 patients 2 years p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 24 publications
(25 reference statements)
0
9
0
Order By: Relevance
“…17 , 36 Emerging studies are now supporting the benefits of SCPs in terms of improving survivors’ comprehension of health information and facilitating communication between survivors, oncologists and PCPs. 37 , 38 , 39 For example, one study demonstrated that the provision of an SCP and professional counselling can effectively motivate survivors of childhood cancer who were treated with cardiotoxic therapies to undergo cardiomyopathy screening. 40 Currently, we are incorporating individualized counselling on personal health risks into a centralized survivorship programme for local survivors of childhood cancer in Hong Kong.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…17 , 36 Emerging studies are now supporting the benefits of SCPs in terms of improving survivors’ comprehension of health information and facilitating communication between survivors, oncologists and PCPs. 37 , 38 , 39 For example, one study demonstrated that the provision of an SCP and professional counselling can effectively motivate survivors of childhood cancer who were treated with cardiotoxic therapies to undergo cardiomyopathy screening. 40 Currently, we are incorporating individualized counselling on personal health risks into a centralized survivorship programme for local survivors of childhood cancer in Hong Kong.…”
Section: Discussionmentioning
confidence: 99%
“…This finding provides an important basis for the development of a personalized ‘Survivorship Care Plan’ (SCP) during the early phase of a patient's cancer survivorship journey 17,36 . Emerging studies are now supporting the benefits of SCPs in terms of improving survivors’ comprehension of health information and facilitating communication between survivors, oncologists and PCPs 37‐39 . For example, one study demonstrated that the provision of an SCP and professional counselling can effectively motivate survivors of childhood cancer who were treated with cardiotoxic therapies to undergo cardiomyopathy screening 40 .…”
Section: Discussionmentioning
confidence: 99%
“…Patients should also be advised not to stop cardioprotective therapies without medical guidance, even if they recover their cardiac function. To help in this complex task, leaflets specifically designed for this context may be used, 832,833 eventually with the aid of digital tools (Figure 47).…”
Section: Patient Information Communication and Self-managementmentioning
confidence: 99%
“…Approaches have been developed to automate the extraction of this information, facilitating the creation of patient‐specific guides 26 . Such care plans have been shown to enhance survivors' understanding of their follow‐up needs 27 and create a crucial reference for future care providers 28 . Use of VD to determine late effects surveillance aligns with the goal to improve patient knowledge of their own health state while taking advantage of available technology and personalized medicine.…”
Section: Discussionmentioning
confidence: 99%